TEMPORALITY OF THE NARRATIVE OF CONTEMPORARY TRAVEL LITERATURE (Based on Cees Nooteboom’s work) - Olena I. Kretova; Pavlo V. Kretov (Alfred Nobel University Journal of Philology)
The article examines the temporality of narrative in the discourse of contemporary travel literature in the context of socio-cultural dynamics associated with the digitalization of life forms, socio-cultural interactions and new models of comprehension, description and representations of reality in literary texts. The emergence of a new picture of the world in the transformations of literary discourse and narrative is problematized. The phenomenon of travel prose by the Dutch writer С. Nooteboom is considered from the perspective of representing the problems of transformation of the temporality of narrative in the contemporary meta-genre of travel literature. The aim of the article is to determine the directions of transformation of the temporality of the narrative in the discourse of modern travel literature in the context of the transformation of life forms of human world and the genre specificity of this meta-genre. The task of the study is to clarify the content of the ontologizing functional of travel literature and its humanistic potential, which is revealed in the existential, axiological, identity and transcendental aspects of the temporal narrative. The research methodology is comprehensive and interdisciplinary. To achieve this goal, historical- literary, historical-philosophical, hermeneutic, narratological, phenomenological, comparative, and narrative methods were used. Research results. In connection with the transformations of the horizon of meanings of modern man (homo digitalis) and the development of the meta-genre of travel literature, we must emphasize the relevance of the worldview influences of literature as an individual and social practice, a segment of social communication and culture on the formation of the identity of modern man and communities. Perhaps, in this context, we can talk about the ontologizing function of travel literature, which, by recording existentials of being here-here in the subjective time of meaning generation, symbolically returns to man the objective space lost by him, expanding the world depicted by new modes of operating with information. The time, the temporality of the narrative of travel literature determines the space of human self-awareness, which also means the problematization of the logical structure of the statement and paradoxically makes the eventfulness of travel not a predicative function of the subject, but an autonomous entity. In the case of travel literature, the temporality of the narrative algorithmizes and structures the reception of reality, which is relevant even for such linguistic constructions that do not directly have markers of temporality, and the ability of such a narrative to configure and reconfigure formats of understanding and meanings of a work of art is emphasized both at the formal and at the content levels. The humanistic potential of travel literature is revealed in the existential, axiological, identity and transcendental aspects of the temporal narrative. The temporal narrative in travel literature is essentially correlated with the principle of intertextuality, fixing modes of interaction, peculiar trigger zones between texts, narratives, discursive and speech practices. The temporal narrative involves the practice of commemoration between the subjects of the texts, including the reader. The temporality of modern travel literature seems to be organized according to the principle of nonlinear discreteness, when the plot unfolding in time and the change of the characters’ localization points necessarily implies a sequence of events that is differentiated by the spheres of somatic presence, reception of empirical reality, and imaginary construction of this reality. The temporality of the narrative of modern travel literature also implies an increased role of the imagological aspect, that is, visualization based on images or descriptions, which reflects the emergence of virtual subgenres of the meta-genre. Also relevant for the modern temporal narrative of travel literature are the oppositions syncretic/ discrete and temporality as a phenomenological marker of human perception and experience of reality and spatiality as a medium of interaction with the Other and Others. The work of С. Nooteboom represents the total optics of travel as a mode of human existence, indissolubly linked to transcendental inquiry and meaning generation, as well as the discovery of identity at all levels – from cultural to gender. Regarding the work of С. Nooteboom, two main approaches can be distinguished, which we can designate as spatial-semiotic and existential-phenomenological. One of them emphasizes the detachment of the Nooteboom traveler as a sign of the meaninglessness and timelessness of travel as a simple change of geographical coordinates, the other interprets travel not as an escape from oneself, but as a search for oneself. The temporal narrative in the writer’s texts can be characterized as extra-historic and transcendent, as well as one that uses the tools of ritual and play. The ontologism of the temporality of narrative in the works of С. Nooteboom is represented in the deployment of simultaneous practices of narrative construction, the use of inversive game techniques and methods inherent in modern and postmodernism. In the later works, there is an influence of the aesthetics of metamodernism, in particular the principle of meta-axis.